RELATIONSHIP BETWEEN CHANGES IN CONCENTRATION OF MALONIC DIALDEHYDE AND BLOOD LIPID SPECTRUM INDICATORS IN PATIENTS WITH STABLE CORONARY HEART DISEAS AND CONCOMITANT ARTERIAL HYPERTENSION - D. A. Volynskyi; I. P. Vakaliuk (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Coronary heart disease (CHD) and concomitant arterial hypertension (AH) are key issues in modern cardiology. At the base of atherogenesis, which plays a crucial role in the progression of both pathologies, oxidative stress and en- dothelial dysfunction lies. Laboratory markers for checking the progressio of these processes are the concentration of total cholesterol, low-density lipopro- tein (LDL) and malonic dialdehyde (MA). Evaluating of the relationship between changes in the levels of these indicators can be a promising direction in the diagnosis of CHD and AH and will help improve and optimize drug treatment. The aim of the study. To identify an association between changes in malonic dialdehyde concentrations and total cholesterol and low-density lipoproteins in patients with stable coronary heart disease with and without concomitant hyper- tension. The study included 131 patients with stable CHD and AH. Patients were divided into 2 groups: 1) 80 patients with stable CHD and concomitant AH; 2) 51 patients with stable CHD without concomitant AH. In the study, we evaluat- ed fluctuations in MA levels. The lipid spectrum of the blood was assessed by the level in the serum of total cholesterol, LDL. The level of MA in the group of patients with concomitant hypertension is significantly higher. We found a weak direct correlation between MA and total cholsterol, MA and LDL in the group of patients with coronary heart disease with concomitant hypertension. We found a weak inverse correlation in patients without abnormal blood pressure fluctua- tions. We were able to establish a relationship between changes in the concentra- tion of MA and total cholesterol and LDL in patients with stable CHD with and without concomitant AH, which confirms the significant effect of oxidative stress and endothelial dysfunction, which are integral companions of hypertension on blood lipid spectrum. Key words: coronary heart disease, hypertension, oxidative stress, malonic dialdehyde, endothelial dysfunction